2015
DOI: 10.1016/j.hrthm.2014.12.035
|View full text |Cite
|
Sign up to set email alerts
|

MRI scanning in patients with new and existing CapSureFix Novus 5076 pacemaker leads: Randomized trial results

Abstract: MRI scans can be performed safely without positioning restrictions in patients with Medtronic CapSureFix Novus 5076 leads connected to an MR-conditional pacemaker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…5 The MR-ICD had specific design and material modifications to reduce interaction with the MRI environment as described elsewhere. 6 Briefly, ferromagnetic material was reduced, a hall sensor replaced the mechanical reed switch, filters to prevent gradient and radiofrequency energy coupling were added, and battery circuitry protection was built in.…”
Section: Study Devicementioning
confidence: 99%
“…5 The MR-ICD had specific design and material modifications to reduce interaction with the MRI environment as described elsewhere. 6 Briefly, ferromagnetic material was reduced, a hall sensor replaced the mechanical reed switch, filters to prevent gradient and radiofrequency energy coupling were added, and battery circuitry protection was built in.…”
Section: Study Devicementioning
confidence: 99%
“…published data from a randomized, multicenter trial of 266 patients implanted with a dual‐chamber MRI conditional pacemaker. Investigators reported no MRI scan‐related complications in 156 patients who underwent 1.5‐T MRI scanning using a series of chest and head sequences at 9–12 weeks after implant . In a single‐center pilot study by Wollmann et al., there were no MRI scan‐related adverse events reported in 36 patients who underwent cMRI scan.…”
Section: Discussionmentioning
confidence: 98%
“…17 Many patients with suspected CS, however, have received a pacemaker, ICD or CRTD, which are contraindicated for CMR, except for the recently introduced MR-conditional pacemaker. 28 Twenty-five patients (48%) could not undergo CMR for the diagnosis of CS, and 34 patients (65%) required cardiac-assist devices. SPECT is an essential tool to assess myocardial injury for such patients.…”
Section: Discussionmentioning
confidence: 99%